Database Preservation Toolkit: A relational database conversion and normalization tool - Ferreira, Bruno (2016)
The Database Preservation Toolkit is a software that automates the migration of a relational database to the second version of the Software Independent Archiving of Relational Databases format. This flexible tool supports the currently most popular Relational Database Management Systems and can also convert a preserved database back to a Database Management System, allowing for some specific usage scenarios in an archival context. The conversion of databases between different formats, whilst retaining the databases' significant properties, poses a number of interesting implementation issues, which are described along with their current solutions. To complement the conversion software, the Database Visualization Toolkit is introduced as a software that allows access to preserved databases, enabling a consumer to quickly search and explore a database without knowing any query language. The viewer is capable of handling big databases and promptly present search and filter results on millions of records. This paper describes the features of both tools and the methods used to pilot them in the context of the European Archival Records and Knowledge Preservation project on several European national archives.